Hilma [videorecording (DVD)] - Hallström, Lasse; Olin, Lena; Hallström, Tora; Chalk, Catherine; De Lisser, Jazzy; Cole, Lily, 1987-; Calder, Rebecca (Actor); Dermody, Maeve; Wlaschiha, Tom; Björk, Anna, 1970-; Holman, Clare; Lundgren, Adam (Juno Films, 2023)
Exploring Hilma af Klint's enigmatic life, now recognized as one of the Western world's first abstract artists. She defied convention to live a free life as an artist in a time when women could not even vote.